Rancang Bangun Sistem Informasi Pendaftaran Siswa Baru Berbasis Web - Nuswantoro, Setio Ardy; Suriansyah, S (STIKOM Tunas Bangsa Pematangsiantar, 2022)
The new student registration system at SMA 2 Muhammadiyah Palangkaraya is still done conventionally, the problem with using a manual system is that manual storage can result in damage or loss of new student registration data and takes a long time to make reports. Problems like this can be overcome by utilizing information technology such as a new student registration information system using the waterfall software development development method which includes the stages of planning, analysis, design, development, implementation, and maintenance. The new student registration system provides information on new student registration, the selection process for new student registration and reporting on the number of new student admissions